Macro-scale modelling of the impact response of 3D woven composites for aerospace applications - Kong, Weiyi (2016)
The objective of this work is to develop a reliable simulation methodology that can be applied to predict the impact response of the components made with 3D textile composites in aero engine applications. Textile composites are excellent candidate materials for the design of aero engine fan containment casings, which are required to sustain the high velocity impact during a fan blade out (FBO) event. This work is focused on a particular form of 3D woven textile composites, in which reinforcement through the thickness is provided by the interlocking weft or warp yarns. An extensive experimental characterisation was conducted for the composites with four different types of reinforcement. The in-plane mechanical properties under the quasi-static tensile, compressive and shear loadings were obtained. The compressive properties at high strain rate were determined in split Hopkinson pressure bar tests. In additional to that, ballistic impact tests were conducted with these composite materials to study their response to high velocity impact loads. The properties determined in the mechanical tests were employed to specify the input data for a commercially available material model in the finite element (FE) software, LS-DYNA. The model was validated by simulating the ballistic impact tests. Good agreement between the predictions and the experimental results was ensured. Once validated, the material model was applied in a range of parametric studies. Since the plate impact tests cannot fully represent the complexity of the FBO event, effects of the projectile shape, the impact obliquity, the target size and the target curvature on the impact performance were investigated by means of parametric studies. To ease the simulation cost encountered during the modelling of a large casing structure, mixed element type analysis (META) was employed for its FE models, where the computationally costly solid elements were coupled with simpler shell elements. The predictive capability of the META models was assessed by comparing their predictions with those of the corresponding solid-element-only models. The study has shown that this method can substantially reduce the simulation time without compromising the accuracy of predictions.